1979
DOI: 10.1113/jphysiol.1979.sp012731
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential, contractile activation and relaxation rates in voltage clamped short muscle fibres of the frog.

Abstract: SUMMARY1. Voltage clamped short (a 15 mm) muscle fibres of the frog can develop maximum tension of 4-3 kg/cm2.2. The time course of contractile responses to prolonged depolarization is markedly dependent on the fibre membrane potential. With sufficiently long pulses the responses present a plateau and a spontaneous relaxation phase.3. At room temperature (20-22 TC), and at membrane potentials of -10 mV the plateau duration is about 2 see and the spontaneous relaxation rate is 0 50 sec-'. At membrane potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 12 publications
5
34
0
Order By: Relevance
“…3c and 4c) may be explained from the viewpoint of the biphasic K contractures; such different effects may be due to the difference between the actions of these divalent cations on the activation mechanism of the initial component and those of the secondary component. CAPUTO (1972CAPUTO ( , 1981 and CAPUTO and FERNANDEZ DE BOLANOS (1979) have proposed a model to interpret the peak tension and the time course of K contractures in terms of an activation and an inactivation mechanism (Caputo model). LUTTGAU and SPIECKER (1979) and COTA and STEFANI (1981, 1982 explained the effect of external Cat + reduction and the effect of Mgt + on the Cat reduction according to this model.…”
Section: Discussionmentioning
confidence: 99%
“…3c and 4c) may be explained from the viewpoint of the biphasic K contractures; such different effects may be due to the difference between the actions of these divalent cations on the activation mechanism of the initial component and those of the secondary component. CAPUTO (1972CAPUTO ( , 1981 and CAPUTO and FERNANDEZ DE BOLANOS (1979) have proposed a model to interpret the peak tension and the time course of K contractures in terms of an activation and an inactivation mechanism (Caputo model). LUTTGAU and SPIECKER (1979) and COTA and STEFANI (1981, 1982 explained the effect of external Cat + reduction and the effect of Mgt + on the Cat reduction according to this model.…”
Section: Discussionmentioning
confidence: 99%
“…There are no descriptions of charge movement or mechanical activation in the different twitch fibre types. However, it has been found that the voltage dependence of tension is similar in slow tonic fibres and twitch fibres (Gilly & Hui, 1980a;Caputo & de Bolanos, 1979; Hodgkin & Horowicz, 1960;Nasledov, 1969). The voltage dependence of charge movement is also similar in slow tonic and twitch fibres, but the maximum charge movement in the tonic fibres is one quarter to one third of that in the twitch fibres (Gilly & Hui, 1980b).…”
Section: Paraplegic Ratsmentioning
confidence: 99%
“…It is now functionally well established that the Ca 2÷ release channel responsible for this process is the ryanodine receptor (RyR) [2,3]. Earlier studies on depolarization-induced Ca 2+ release (or contraction) showed that Ca 2÷ release is turned off by membrane repolarization [4][5][6][7][8], and based on this evidence the rate of Ca 2÷ release was estimated. Since Ca 2+ release flux started to decay within a millisecond of repolarization, there seemed to be a direct mechanical coupling between the voltage sensor and the release channel [5,9].…”
Section: Introductionmentioning
confidence: 99%